Univocity, Exhaustion and Failing Better: Reading Beckett with Disability Studies. Issue 2 (September 2018) - Levin, Yael
Abstract : The emergence of theories of disability in the last decades has rendered figurative interpretation suspect; neglect of literal and material truths has been hailed unethical, the exercising of an ableist bias that utilizes physical impairment as a rhetorical device. Any attempt to reconcile such critical concerns with Beckett's writing must take cognizance of an essential incongruity between the socially conscripted theoretical framework and aesthetic experimentation, between a mimetic fidelity to lived experience and an art of non-relation. The essay suggests that Beckett's poetics of exhaustion and its rejection of substitution and analogy in the interpretation of figures allows us to think beyond the interdisciplinary divide. The body is not imagined as a stand-in or receptacle for philosophical ideas but rather as the substrate upon and with which these ideas evolve and change. The text maintains the materiality of mental and physical impairments at the same time that it loads them with a variety of different metonymical connections. Such a stylization of excess and accumulation serves to release disability from existing stereotypes and predetermined moral judgment. It does so while sidestepping an impasse in disability studies, between the need to valorise overcoming, on the one hand, and the need to support the inability to do so, on the other. Neither extolling the supercrip nor championing inability, Beckett allows his readers to productively imagine what it might mean to fail better.